2014
DOI: 10.4314/star.v3i3.4
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotany and Germplasm Collection of Two Genera of <i>Cocoyam (Colocasia</i> [Schott] and <i>Xanthosoma</i> [Schott], Araceae) in Edo State Nigeria

Abstract: Article Information Ethnobotany describes the realm between human interactions with plant in their environment. Colocasia [Schott] and Xanthosoma [Schott] (Araceae) are important staples in Nigeria. This study aims to document the traditional knowledge base of these crops amongst tribes in Edo state. Using random stratified sampling technique, fifty respondents were selected and primary data obtained through semi structured questionnaire. Fifty-four cocoyam (61.11 % Xanthosomaand and 38.89 % Colocasia) germpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(10 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The meanings of the local names were linked either with the area of collection or the crop"s particular trait such as the growth condition. Similar study conducted in Edo State, Nigeria indicated that the local people distinguish cocoyam local types by area of collection (Osawaru and Ogwu, 2015). Various local names have also been used for X. sagittifolium worldwide (Morton, 1972;Giacometti and Leon, 1994;Mayo et al, 1997;Raemaekers, 2001;Maundu et al, 2009;Lebot, 2009;Quero-Garcia et al, 2010).…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…The meanings of the local names were linked either with the area of collection or the crop"s particular trait such as the growth condition. Similar study conducted in Edo State, Nigeria indicated that the local people distinguish cocoyam local types by area of collection (Osawaru and Ogwu, 2015). Various local names have also been used for X. sagittifolium worldwide (Morton, 1972;Giacometti and Leon, 1994;Mayo et al, 1997;Raemaekers, 2001;Maundu et al, 2009;Lebot, 2009;Quero-Garcia et al, 2010).…”
Section: Discussionmentioning
confidence: 91%
“…Most of the farmers" preferred traits of the study survey are the traits of preference by Nigerian farmers (Osawaru and Ogwu, 2015). In another way round, in Ethiopia, farmers disliked traits such as low palatability, corm inedibility, hardness and acridity hinder its potential to be a major crop.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations